New insight into the metabolic mechanism of a novel lipid-utilizing and denitrifying bacterium capable of simultaneous removal of nitrogen and grease through transcriptome analysis - Tong, Yaobin; Li, Yiyi; Qin, Wenpan; Wu, Shengchun; Xu, Weiping; Jin, Peng; Zheng, Zhanwang (Frontiers in Microbiology, 2023)
Introduction Issues related to fat, oil, and grease from kitchen waste (KFOG) in lipid-containing wastewater are intensifying globally. We reported a novel denitrifying bacterium Pseudomonas CYCN-C with lipid-utilizing activity and high nitrogen-removal efficiency. The aim of the present study was aim to explore the metabolic mechanism of the simultaneous lipid-utilizing and denitrifying bacterium CYCN-C at transcriptome level. Methods We comparatively investigated the cell-growth and nitrogen-removal performances of newly reported Pseudomonas glycinae CYCN-C under defined cultivation conditions. Transcriptome analysis was further used to investigate all pathway genes involved in nitrogen metabolism, lipid degradation and utilization, and cell growth at mRNA levels. Results CYCN-C could directly use fat, oil, and grease from kitchen waste (KFOG) as carbon source with TN removal efficiency of 73.5%, significantly higher than that (60.9%) with sodium acetate. The change levels of genes under defined KFOG and sodium acetate were analyzed by transcriptome sequencing. Results showed that genes cyo, CsrA, PHAs, and FumC involved in carbon metabolism under KFOG were significantly upregulated by 6.9, 0.7, 26.0, and 19.0-folds, respectively. The genes lipA, lipB, glpD, and glpK of lipid metabolic pathway were upregulated by 0.6, 0.4, 21.5, and 1.3-folds, respectively. KFOG also improved the denitrification efficiency by inducing the expression of the genes nar, nirB, nirD, and norR of denitrification pathways. Conclusion In summary, this work firstly provides valuable insights into the genes expression of lipid-utilizing and denitrifying bacterium, and provides a new approach for sewage treatment with reuse of KFOG wastes.